Case Report: Traumatic Abdominal Hernia Correction in a french poodle canine (Revista Sistemas de Producción Agroecológicos, 2023)
The case of a French poodle canine that suffered a car accident, which caused an open abdominal trauma, injuring the muscular wall and exposing the peritoneal cavity, is presented. He was admitted to the Veterinary Clinical Center of the University of the Llanos, where a clinical examination was performed, which determined a left lateral traumatic abdominal hernia. Subsequently, the surgical correction "Traumatic abdominal herniorrhaphy" was performed and during the intervention peritonitis was evidenced, due to bacterial contamination of the peritoneal fluid. Consequently, the patient had postoperative complications for which he underwent surgery three more times. After these surgical procedures, the administration of Ceftriaxone was taken as a therapeutic plan, since there was no evolution, the drug Meropenem was continued and finally the patient recovered satisfactorily.
Keywords: Traumatic abdominal hernia; surgical reconstruction; peritonitis